Evaluation of Some Serological Indicators in Women with Polycystic Ovary Syndrome in Baquba , Iraq (Bangladesh Journal of Medical Science, 2023)
Polycystic ovary syndrome (PCOS) is receiving increasing attention, due to its association with many health troubles such as infertility and diabetes. The purpose of our study is to estimate the serum level of some indicators in women patients with PCOS. This study was conducted prospectively on 70 participating women who attended Al-Batool Teaching Hospital in Baquba (Iraq), with ages between (18-35) years, from February 2020 to November 2022. All the participating women were separative into two groups: )Control( group included 30 healthy women,and (PCOS) group included 40 women suffer from polycystic ovary syndrome. Ultrasound and analyzes of the sex hormones of the participants were used to confirm the detection of PCOS. Serological biomarkers were measured for both groups, including histidine, ferritin, follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin, and estrogen (E2). Results proven a notable reduction in the serum levels of hepcidin and FSH in PCOS group compared to healthy control group. In contrast, a considerable increases in levels of LH, prolactin, ferritin, and estrogen E2 hormone were observed in patients with PCOS. It was founded that these biochemical indicators may be a reliable diagnostic measure for polycystic ovary syndrome cases.Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.4-9